Atenção farmacêutica em pacientes hipertensos: Estudo piloto - Modé, Carolina Luiza [UNESP]; Lima, Mariana Moreira [UNESP]; Carnavalli, Flávia [UNESP]; Trindade, Ariane Biolcati [UNESP]; de Almeida, Adélia Emília [UNESP]; Chin, Chung Man [UNESP]; dos Santos, Jean Leandro [UNESP] (My University, 2015)
Arterial Hypertension (HBP) has a high prevalence. Despite being considered one of the major modifiable risk factors, has low control rates. Adherence to treatment added to the correct use of medicines are important factors for therapeutic success. The research aimed to deploy a pilot study of pharmaceutical care for hypertensive patients in private pharmacy during five months using Dáder method. Patients (n = 20) were divided into “control group” and “intervention group”. Both groups had blood pressure (BP) measured at baseline and at the end, but only the intervention group received pharmacotherapy follow-up and had BP measured three times a week. Of all patients, 70% (14) had some sort of Negative Outcomes associated with Medication (NOM). The NOM 1, which is related to therapy non-adherence was the most found. The majority of pharmaceutical interventions (73.7%) conducted were about health education. It was noted that patients have greater adherence to therapy after knowing better their illnesses and their medications. Among the 20 patients who participated in the pilot study, 45% had uncontrolled BP (≥140x90mmHg) in the first interview. After pharmaceutical interventions this number was reduced to 20%. In the intervention group, the mean systolic and diastolic BP had a significant reduction of 17 mmHg and 8mmHg, respectively. It can be concluded that pharmaceutical interventions to promote improvement in blood pressure levels are effective in order to optimize therapeutic outcomes as well as achieving improvements in the quality of life of patients.
Pharmaceutical care in hypertensive patients: A pilot study
Keywords: Hypertension; Negative outcomes associated with medication; Pharmaceutical care; Pharmacotherapeutic follow-up